Characterization of Native and Human Serum Albumin-Bound Lysophosphatidic Acid Species and Their Effect on the Viability of Mesenchymal Stem Cells In Vitro - Aliz Majer; Julianna Pesthy; Balázs Besztercei; Adél Hinsenkamp; László Smeller; Zsombor Lacza; Zoltán Benyó; Éva Ruisanchez; István Hornyák (Applied Sciences, 2022)
Scaffolds can provide a healthy environment for cell attachment, differentiation, proliferation, and migration in vitro and in vivo. Lysophosphatidic acid (LPA) is a naturally occurring bioactive phospholipid that is present in the serum mainly bound to albumin. The present study aims to investigate the biocompatibility of LPA. It also aims to determine the effect of different LPA species on the proliferation and migration of human bone marrow-derived mesenchymal stem cells (hBM-dMSCs) for LPA and human serum albumin (HSA) containing bone scaffold development. The HSA-LPA complex formation was assessed using Fourier-transform infrared (FTIR) spectroscopy. The effect of 18:1, 18:2, or 16:0 LPA alone, or in combination with 4% HSA, on cell viability and proliferation was determined by XTT. The cell migration was examined in a wound healing assay. The changes in the FTIR spectra of LPA-HSA compositions, compared with HSA alone, indicate the complex formation between the components. Our study showed that 18:1, 18:2, and 16:0 LPA species had no cytotoxic effects up to 10 µM concentration. The different LPA species increased the proliferation of hBM-dMSCs in a dose-dependent manner when administered in the presence of HSA, without an effect on the migration of this cell type. These findings make the in vivo application of LPA-HSA complex promising for bone regeneration.